2014
DOI: 10.1002/ajim.22315
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of rotator cuff syndrome in a French working population

Abstract: This descriptive study showed that a high percentage of workers recovered and several personal and work-related factors were associated with persistent RCS. Larger prospective studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(65 reference statements)
2
5
1
1
Order By: Relevance
“…Conversely, strong social support was linked to a shorter sick leave duration, still in the single‐factor model. Nevertheless, unlike for Bodin et al, 6 low decision latitude was not a significantly pejorative work characteristic in our study.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Conversely, strong social support was linked to a shorter sick leave duration, still in the single‐factor model. Nevertheless, unlike for Bodin et al, 6 low decision latitude was not a significantly pejorative work characteristic in our study.…”
Section: Discussioncontrasting
confidence: 92%
“…Other works have reported longer sick leave durations, 7 up to 9.8 months, as well as shorter periods of 5 months 13,46 . According to the authors, the short duration reported by Bodin et al 6 could be explained by the low severity of cases in the population studied.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In the working population, 30% report daily shoulder pain during the previous year [2]. The pain can persist for months or even years in about a third of cases [3,4]. Lasting aches, intense pain and severe functional limitations are noted as factors of poor prognosis regarding recovery and repercussion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%